2017
DOI: 10.1136/gutjnl-2017-313789
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induces proinflammatory dysbiosis: transmission of inflammatory susceptibility by host cytokine induction

Abstract: Objective Radiation proctitis (RP) is a complication of pelvic radiotherapy which affects both the host and microbiota. Herein we assessed the radiation effect on microbiota and its relationship to tissue damage using a rectal radiation mouse model. Design We evaluated luminal and mucosa-associated dysbiosis in irradiated and control mice at two postradiation time points and correlated it with clinical and immunological parameters. Epithelial cytokine response was evaluated using bacterial-epithelial co-cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
197
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 236 publications
(220 citation statements)
references
References 38 publications
10
197
2
Order By: Relevance
“…Radiotherapy is one of the most successful cancer therapies, but it may give rise to severe tissue damage that limits its use. Small intestine epithelium has high sensitivity to radiation and is the major site of radiation‐induced injury due to frequent intestinal epithelial turnover . A shift in intestinal microbiota composition after radiotherapy was observed in mice .…”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 99%
“…Radiotherapy is one of the most successful cancer therapies, but it may give rise to severe tissue damage that limits its use. Small intestine epithelium has high sensitivity to radiation and is the major site of radiation‐induced injury due to frequent intestinal epithelial turnover . A shift in intestinal microbiota composition after radiotherapy was observed in mice .…”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 99%
“…The data presented by Gerassy-Vainberg et al 10 are reminiscent of what is observed in IBD in which the dysbiotic microbiota is a strongly suspected actor in disease evolution. Indeed, the radiation-induced dysbiosis described is reminiscent to IBD and to colitis models in mice with notably a decreased abundance in Firmicutes and an increased abundance in Proteobacteria .…”
mentioning
confidence: 67%
“…Consequent to dysbiosis, intestinal inflammation in both disease entities (ie, radiation-induced enteritis and IBD) may be partly driven by IL-1 receptor signalling 10 13. Thus, the results presented by Gerassy-Vainberg et al 10 suggest that common mechanism(s) are engaged in intestinal inflammation of different origin which culminate in dysbiosis and consecutive derangements in the host–microbiota crosstalk.…”
mentioning
confidence: 97%
See 2 more Smart Citations